Analisis Nilai Tambah Dan Penentuan Prioritas Produksi Produk Kopi Di Arca Coffee Kintamani Bangli - Situmeang, Vera Wati; Satriawan, I Ketut; Suryawan Wiranatha, A. A. P. Agung (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
The purpose of this study was to calculate the added value generated in the processing of coffee products at Arca Coffee and determine production priorities in the processing of coffee products at Arca Coffee. This study uses the Hayami method to analyze added value. Demand forecasting uses the moving average method, exponential smoothing method, trend project method (linear trend) as well as Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE) to calculate the error value in the forecasting method used to determine the best forecasting method. The results showed that the added value generated in the processing of natural coffee bean products, honey coffee beans, and whole washed coffee beans at Arca Coffee respectively was Rp 9,200/kg, Rp 9,100/kg, and Rp 8,000/kg with successive value-added ratios of 40.00%, 39.57%, and 36.36% and the priority of production in processing coffee products at Arca Coffee was full washed coffee beans respectively, honey coffee beans, and natural coffee beans.